2006
DOI: 10.1073/pnas.0604661103
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants protect PINK1 -dependent dopaminergic neurons in Drosophila

Abstract: Parkinson's disease (PD) is the most frequent neurodegenerative movement disorder. Mutations in the PINK1 gene are linked to the autosomal recessive early onset familial form of PD. The physiological function of PINK1 and pathological abnormality of PDassociated PINK1 mutants are largely unknown. We here show that inactivation of Drosophila PINK1 (dPINK1) using RNAi results in progressive loss of dopaminergic neurons and in ommatidial degeneration of the compound eye, which is rescued by expression of human PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
143
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 40 publications
13
143
1
Order By: Relevance
“…One explanation for this variation in phenotype is that genetic background may play an important role in the severity and͞or penetrance of the dPINK1 phenotype. Perhaps the degree of baseline oxidative damage depends on genetic background, which would be consistent with the finding by Wang et al (6) that antioxidants can protect against even the most severe dPINK1 loss-of-function phenotype. It also has been suggested that the environment and genetic background similarly play a key role in the age of onset and severity of PD in humans.…”
Section: Pink1 As a Discovery Toolsupporting
confidence: 77%
See 4 more Smart Citations
“…One explanation for this variation in phenotype is that genetic background may play an important role in the severity and͞or penetrance of the dPINK1 phenotype. Perhaps the degree of baseline oxidative damage depends on genetic background, which would be consistent with the finding by Wang et al (6) that antioxidants can protect against even the most severe dPINK1 loss-of-function phenotype. It also has been suggested that the environment and genetic background similarly play a key role in the age of onset and severity of PD in humans.…”
Section: Pink1 As a Discovery Toolsupporting
confidence: 77%
“…The Wang et al (6) study complements recent parallel reports (7)(8)(9) examining the phenotypes of dPINK1 mutant flies to provide new insights into the integrated function of cytoplasmic and mitochondrial proteins in the etiology of PD. An important puzzle in the etiology of PD is that it seems to involve both cytoplasmic and mitochondrial functions, yet it is unclear how these functions might be linked.…”
Section: The Parkinson Pathwaysupporting
confidence: 62%
See 3 more Smart Citations